PENERAPAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN PAI DI MASA PANDEMI COVID-19 DI SMAN 1 KURIPAN LOMBOK BARAT - Muhammad Yuslih; Paida Paida (MA'ALIM: Jurnal Pendidikan Islam, 2021)
This study aims to determine the application of a scientific approach in PAI learning for class X during the covid 19 pandemic. This type of research uses descriptive qualitative research by choosing a location at SMAN 1 Kuripan Dusun Tegal, Jagaraga Village, Kec. Kuripan, Kab. West Lombok. Sources of data in this study were PAI teachers and students of class X, the principal and the Deputy Head of Curriculum. The data collection method used is the method of observation, interviews, and documentation. The results showed that the application of a scientific approach to PAI learning in class X during the Covid-19 pandemic at SMAN 1 Kuripan used online and offline learning processes. In its implementation, through the first several stages, the teacher sends material in the form of videos or reading materials related to the material through WhatsAPP, then students observe the material. Second, ask about material that has not been understood either through Chat WA/Voice Chat. Third, associating/reasoning students are given tasks related to the material. Fourth, students present the assignment via WhatsApp. Fifth, students draw conclusions from the results of the presentation. The implementation of learning using a scientific approach in PAI learning during the COVID-19 pandemic has been carried out even though it has not been maximized. The obstacles in the application of the scientific approach include the lack of student activity in the learning process, and limited facilities and infrastructure.